2016
DOI: 10.3390/w8100465
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Constructed Wetlands for Removal of Antibiotics from Saline Aquaculture Effluents

Abstract: Abstract:This work aimed to evaluate the potential of constructed wetlands (CWs) for removal of antibiotics (enrofloxacin and oxytetracycline) and antibiotic resistant bacteria from saline aquaculture wastewaters. Removal of other contaminants (nutrients, organic matter and metals) and toxicity reduction and the influence of antibiotics with these processes were evaluated. Thus, nine CWs microcosms, divided into three treatments, were assembled and used to treat wastewater (doped or not with the selected antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 41 publications
(50 reference statements)
0
21
0
3
Order By: Relevance
“…For instance, physiological drought, nutrient deficiency, and cell structure damage can occur, and, especially, plant roots can be immediately injured by high salinity [3]. Phragmites australis, a representative wetland plant, is found in both freshwater and saline habitats [4] and even adapts to high-salinity regions. Many previous studies have shown that P. australis is easily propagated by seed dispersion and vegetatively propagated from vertical and horizontal rhizomes and stolons [5].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, physiological drought, nutrient deficiency, and cell structure damage can occur, and, especially, plant roots can be immediately injured by high salinity [3]. Phragmites australis, a representative wetland plant, is found in both freshwater and saline habitats [4] and even adapts to high-salinity regions. Many previous studies have shown that P. australis is easily propagated by seed dispersion and vegetatively propagated from vertical and horizontal rhizomes and stolons [5].…”
Section: Introductionmentioning
confidence: 99%
“…The systems were able to remove the antibiotics and antibiotic-resistant bacteria, and reduce wastewater toxicity. In addition, no impact of the antibiotic presence was observed on the removal of nutrients, organic matter, and metal, with percentages being similar between exposed and unexposed microcosms [18].…”
Section: This Special Issuementioning
confidence: 89%
“…Bôto et al [18] used CW microcosms to evaluate CWs for the removal of antibiotics (enrofloxacin and oxytetracycline) and antibiotic-resistant bacteria from saline aquaculture wastewaters. The systems were able to remove the antibiotics and antibiotic-resistant bacteria, and reduce wastewater toxicity.…”
Section: This Special Issuementioning
confidence: 99%
“…CWs can be operated under different flow configurations, with different macrophytes and different solid supports, and it is thus possible to design specific configurations applicable to remove certain pollutants from effluents [107,108] (Figure 3). CWs can also represent an alternative strategy to reduce or remove antibiotics and ARB and ARGs in wastewater [109,110]. These systems exhibit a wide range of efficiencies (from 59 to almost CWs can also represent an alternative strategy to reduce or remove antibiotics and ARB and ARGs in wastewater [109,110].…”
Section: Constructed Wetlandsmentioning
confidence: 99%